Indications and practices of Cesarean Sections in a French region – The Robson classification. (13th November 2019) - Laurent, E; Lecuyer, A I; Baron, S; Diguisto, C; Turpin, D; Potin, J; Grammatico-Guillon, L
Abstract: Background: Cesarian-section (CS) deliveries, although sometimes vital, are associated with increasing immediate- and long-term maternal and/or neonatal risks. The objective was to describe the indications of scheduled CS, measure the potentially avoidable CS and study the rate variations between maternities in one French region, Centre Val-de-Loire (CVL). Methods: A cross-sectional study was conducted from September 2016 to February 2017. Information about all CS performed in the maternities of the region was collected: medical history, indication, schedule. Data collection was completed with the 2016 regional birth data repository (25, 864 deliveries, including 19.2% of CS, among which 7.0% were scheduled). CS were classified according to the pre-existing risk high or low of CS as defined by the Robson classification. Results: During the study period, 1, 979 CS (18.6% of deliveries) were performed, of which 762 were scheduled (7.1% of deliveries). The main indications for planning a CS were: scarred uterus (60%, of which 56% with only one previous CS) or breech presentation (25%), considered at high risk of CS according to the Robson classification. For these two contexts, the regional birth repository showed decreasing scheduled CS rates from high to low level of maternities' expertise. Remarkly, 22 nulliparous women with a single cephalic pregnancy in spontaneous labor before term (Robson's low risk of CS) had a CS performed for unfavorable pelvimetry (0.2% of deliveries). Conclusions: This study allowed identifying specific potential interventions: targeted CS on scarred uterus with only one previous CS or breech presentation, as recommended by national guidelines, and targeted use of radiologic pelvimetry. The Robson classification must be widely used to assess practices through cautious maternity comparisons to improve quality of care. Key messages: Although potentially avoidable c-sections are rare, interventions were identified: targeted CS on uterus with one previous CS or breech presentation, targeted use of radiologic pelvimetry. The Robson classification must be widely used to assess practices, in order to improve healthcare quality.